N-aryl 2-aryloxyacetamides as a new class of fatty acid amide hydrolase (FAAH) inhibitors - Sunduru, Naresh (J Enzyme Inhib Med Chem, 2017)
Fatty acid amide hydrolase (FAAH) is a promising target for the development of drugs to treat neurological diseases. In search of new FAAH inhibitors, we identified 2-(4-cyclohexylphenoxy)-N-(3-(oxazolo[4,5-b]pyridin-2-yl)phenyl)acetamide, 4g, with an IC(50) of 2.6 µM as a chemical starting point for the development of potent FAAH inhibitors. Preliminary hit-to-lead optimisation resulted in 2-(4-phenylphenoxy)-N-(3-(oxazolo[4,5-b]pyridin-2-yl)phenyl)acetamide, 4i, with an IC(50) of 0.35 µM.